Soi personnel et soi collectif : les sources d’un malentendu - Fabio Lorenzi-Cioldi (Terrains/Théories)
In this article, I claim that social identity theory, a founding contribution to the social-psychological study of intergroup differentiation, has suffered from a lack of consideration of notions pertaining to the hierarchical arrangement of groups in the society (social status, power, and domination). The major role of social hierarchies in accounting for social identification is then illustrated by a series of recent experimental and field studies. The findings from this research highlight the complexity of social identifications. They show that members of the high-status group emphasize identifications at the personal level, whereas members of the low-status group emphasize more collective and depersonalized identifications. These tendencies lead to a broader conceptualization of the notion of social group.